Mechanical properties and characterizations of polypropylene based composite - Norul Amierah, Nor Zamani (2016)
Polypropylene based composite is widely applied in the industry especially in automotive applications, due to their excellent mechanical properties, low cost and can be easily produced. This research is directed towards obtaining the mechanical properties and characterisation of polypropylene based composite for different objectives. Though the first objective was to prepare and fabricate the specimen with five different composites. The fabrications of specimen are useful in designing products where quality of the composite cannot be compromised. In this research, the mechanical properties that were studied include tensile properties and impact properties. Surface fracture of specimen were obtained and used to predict these properties as functions of corresponding compositions of the composites by using optical microscope. In this research, the samples were prepared by injection moulding process with standard of ASTM D638. Pure polypropylene, nylon and glass fibre were mixed according to the desired mixing ratio and injection moulded into dog bone-shaped in order to test its Ultimate Tensile Strength (UTS) and Impact Strength of the mixed materials. After the specimens produced, they undergo the tensile test and impact test in order to test their mechanical properties. As a result, it is concluded that the specimen of pure polypropylene obtain high tensile stress at maximum load and high impact strength. Thus, the results obtained shown an opposite output compared to the hypothesis due to the problem during fabrication of the specimens. The fractured specimens for both testing have undergone the microstructure analysis. The surface fractured was analysed by using optical microscope in order to see the different surface between the composites. Therefore, it is concluded that the fractured surface of 100% polypropylene have smooth surface compared to the specimen with contain of nylon and glass fibre.